Impact of dividend policy on financial performance of listed deposit money banks in Nigeria - Mustapha, Fatima Gana; Abdullahi, Sadiq Rabiu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This paper examines the effect of dividend policy on financial performance of listed deposit money banks in Nigeria. The data were collected from seven listed money deposit banks for a period of seven years from 2015 to 2021. The result indicates that dividend per share significantly and positively influenced the financial performance of listed deposit money banks in Nigeria. it also showed that firm size is negative and significantly related with firm financial performances. This result implies that larger firms are so reluctant about improving performance. On the other hand, the result of leverage reveals a positive significant relationship with financial performance. Thus, this finding is important to shareholders and potentials investors.